2020
DOI: 10.1039/d0ob00054j
|View full text |Cite
|
Sign up to set email alerts
|

Newly synthesized 3-sulfenylindole derivatives from 4-hydroxydithiocoumarin using an oxidative cross dehydrogenative coupling reaction (OCDCR): potential lead molecules for antiproliferative activity

Abstract: Synthesis of 3-sulfenyl indole derivatives is achieved through oxidative cross-dehydrogenative coupling reaction. A few such newly synthesized compounds have also exhibited anti-proliferative activity via reactive oxygen species mediated cell damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…[105] Indole-thioflavone hybrids 66a,b (IC 50 : 6.32 and 7.21 µM) possessed potent activity in fighting against MCF-7 cancer cells, with the SAR demonstrated that the introduction of substituents into C-5 position of indole moiety reduced the activity. [106] Mechanistically, these hybrids elevated ROS and caused cell damage leading to cell death. [108] Inducing apoptosis was the mechanism via which hybrid 69 suppressed cell proliferation.…”
Section: Miscellaneous Indole/isatin Hybridsmentioning
confidence: 99%
“…[105] Indole-thioflavone hybrids 66a,b (IC 50 : 6.32 and 7.21 µM) possessed potent activity in fighting against MCF-7 cancer cells, with the SAR demonstrated that the introduction of substituents into C-5 position of indole moiety reduced the activity. [106] Mechanistically, these hybrids elevated ROS and caused cell damage leading to cell death. [108] Inducing apoptosis was the mechanism via which hybrid 69 suppressed cell proliferation.…”
Section: Miscellaneous Indole/isatin Hybridsmentioning
confidence: 99%
“…Catalytic amount of molecular iodine was used along with TBHP in presence of 10 mol% CuBr 2 as an additive at room temperature (Scheme 68). [126] Utilising the concept of sulfonylation, Peddinti and Aegurla demonstrated an iodine/(TBHP)-mediated protocol for the construction of C(sp 2 )À SO 2 and C(sp 3 )À SO 2 bonds through a radical pathway and an ionic pathway, respectively. The denitrative sulfonylation (DNSF) of β-nitrostyrenes with arylsulfo + nylhydrazides proceeded via addition-elimination pathway.…”
Section: Cà S Bond Formation Reactionsmentioning
confidence: 99%
“…Catalytic amount of molecular iodine was used along with TBHP in presence of 10 mol% CuBr 2 as an additive at room temperature (Scheme 68). [126] …”
Section: Sulfenylation/sulfonylation Reactionsmentioning
confidence: 99%
“…Due to the nucleophilic nature of the ring, a range of electrophilic sulfur species are employed for the functionalization of C-3 and C-2 position. These conditions involve transition metals catalysts, [37] iodine, [38] strong bases, [39] and photocatalysts. [40] However few examples have been described using photo promoted cascades.…”
Section: Recent Developments On the Photocatalytic Synthesis Of Indoles Oxindoles And Indolinesmentioning
confidence: 99%